Binding affinity in drug design: experimental and computational techniques. (3rd August 2019) - Kairys, Visvaldas; Baranauskiene, Lina; Kazlauskiene, Migle; Matulis, Daumantas; Kazlauskas, Egidijus
ABSTRACT: Introduction : In pharmaceutical design where future drugs are developed by targeting a specific chosen protein, the evaluation of ligand affinity is crucial. For this very purpose are a multitude of diverse methods which are continuously being improved, which, in turn, makes it difficult to choose which techniques to use in practice. Areas covered : In this review, the authors discuss both experimental and computational approaches for affinity evaluation. Basic principles, general limitations and advantages, as well as main areas of application in drug discovery, are overviewed for some of the most popular ligand binding assays. The authors further provide a guide to affinity predictions, collectively covering several techniques that are used in the first stages of rational drug design. Expert opinion : All affinity estimation methods have limitations and advantages that partially overlap and complement one another. Some of the suggested best practices include cross-verification of data using at least two different techniques and careful data interpretation.